Functional Threshold Power Estimated from a 20-minute Time-trial Test is Warm-up-dependent - Tramontin, Artur Ferreira; Borszcz, Fernando Klitzke; Costa, Vitor (International Journal of Sports Medicine, 2021)
This study investigated the influence of different warm-up protocols on functional threshold power. Twenty-one trained cyclists (˙VO2max=60.2±6.8 ml·kg−1·min−1) performed an incremental test and four 20-min time trials preceded by different warm-up protocols. Two warm-up protocols lasted 45 min, with a 5-min time trial performed either 15 min (Traditional) or 25 min (Reverse) before the 20-min time trial. The other two warm-up protocols lasted 25 min (High Revolutions-per minute) and 10 min (Self-selected), including three fast accelerations and self-selected intensity, respectively. The power outputs achieved during the 20-min time trial preceded by the Traditional and Reverse warm-up protocols were significantly lower than the High Revolutions-per-minute and Self-selected protocols (256±30; 257±30; 270±30; 270±30 W, respectively). Participants chose a conservative pacing strategy at the onset (negative) for the Traditional and Reverse but implemented a fast-start strategy (U-shaped) for the High revolutions-per-minute and Self-selected warm-up protocols. In conclusion, 20-min time-trial performance and pacing are affected by different warm-ups. Consequently, the resultant functional threshold power may be different depending on whether the original protocol with a 5-min time trial is followed or not.
Keywords: cycling; time trial; performance; pacing